Communication Behavior of International Studeraksi Sosial Mahasiswa Afghanistan di IPB Universityn Students at IPB University - Solihin, Olih; Aminah, Ratih Siti; Sadjijo, Priyono; Taufik, Iswan; siti aminah, ratih (Global Political Studies Journal, 2025)
This research explores the communication behaviors of Afghan international students at IPB University, focusing on their cross-cultural social interactions. International students often encounter communication barriers due to differences in language, cultural norms, and social values, which can impact their academic adaptation. This study employed a qualitative approach, conducting in-depth interviews with five Afghan students. The findings indicate that students adopt verbal and nonverbal communication strategies reflecting their native culture while simultaneously attempting to adjust to local customs. They experience challenges like language limitations, cultural misunderstandings, and social stereotypes but show adaptive capacity through partial assimilation and participation in multicultural communities. Utilizing Face-Negotiation Theory and Cultural Adaptation Theory, the study analyzes their identity negotiation and social relationships. The research suggests that the presence of international students contributes to Indonesia's cultural diplomacy, with universities acting as non-state actors. Therefore, institutional support and cultural mentoring programs are essential to strengthen educational diplomacy and create an inclusive, globally competitive campus. Keywords— Adaptation, Cultural diplomacy, Cross-cultural communication, Intercultural communication, international students, IPB University